Osteocalcin Ameliorates Motor Dysfunction in a 6-Hydroxydopamine-Induced Parkinson’s Disease Rat Model Through AKT/GSK3β Signaling - Guo, Xing-zhi; Shan, Chang; Hou, Yan-fang; Zhu, Geng; Tao, Bei; Sun, Li-hao; Zhao, Hong-yan; Ning, Guang; Li, Sheng-tian; Liu, Jian-min (Frontiers in Molecular Neuroscience, 2018)
Osteoblasts derived osteocalcin (OCN) is recently reported to be involved in dopaminergic neuronal development. As dopaminergic neuronal injury in the substantia nigra (SN) is a pathological hallmark of Parkinson’s disease (PD), we investigated whether OCN could exert protective effects on 6-hydroxydopamine (6-OHDA)-induced PD rat model. Our data showed that the OCN level in the cerebrospinal fluid in PD rat models was significantly lower than that in controls. Intervention with OCN could improve the behavioral dysfunction in PD rat models and reduce the tyrosine hydroxylase loss in the nigrostriatal system. In addition, OCN could inhibit the astrocyte and microglia proliferation in the SN of PD rats. In vitro studies showed that OCN significantly ameliorated the neurotoxicity of 6-OHDA through the AKT/GSK3β signaling pathway. In summary, OCN plays a protective role against parkinsonian neurodegeneration in the PD rat model, suggesting a potential therapeutic use of OCN in PD.